Terapi Farmakologis Tinea Korporis pada Anak - Fernandya Sylvia Nurindi; Rasmi Zakiah Oktarlina; Roro Rukmi WP (Medula, 2020)
Tinea corporis is a superficial fungal infection that attacks glabrous skin except the palms, soles of the feet and between thighs. Tinea corporis occurs in all age, but the highest incidence is in children and adolescents. The incidence of tinea corporis also depends on various factors, such as geographic conditions, climate, population, lifestyle, migration, culture, education and socioeconomic levels. The clinical features include the reddish spots with squama or central healing on its central accompanied by itching that is especially felt when sweating. The management of tinea corporis is divided to non-pharmacologic and pharmacologic. Pharmacologic therapy used for tinea corporis is a topical antifungal group imidazole, allylamine or benzylamine. The use of systemic antinfungal for tinea corporis only if the lesion is widespread and topical treatment is unsuccessful.